Unmasking Political Branding of Comedian Candidates in Indonesia: A Discourse Network Analysis - Isni Hindriaty Hindarto; Eriyanto Eriyanto (Profetik: Jurnal Komunikasi, 2025)
In Indonesia, the representation of comedians in the legislature remains limited, although the 2024 elections saw a notable increase in comedian candidates. They are, however, still under-represented. The recent increase in the number of comedians running for office reinforces the urgency of research on how  this phenomenon is understood, negotiated, and debated in the public sphere. This research examines the construction of discourse in relation to the portrayal of comedians in Indonesian politics through online media coverage. Discourse Network Analysis (DNA) is employed to map  discourse coalitions and the connections between actors that shape public perception. An analysis of 80 online news articles, published between January and October 2023, identified 548 statements from various actors, which were then categorised based on their roles and affiliations. Network metrics, specifically weighted density and degree centrality, confirm high coalition cohesion and the dominance of the popularity frame. This resulting network revealed two distinct  actor groups of 44 each. One coalition comprising  comedians and politicians leverages popularity as a form of political capital to secure public endorsement and media coverage. In contrast, a coalition of academics, politicians, and media commentators has condemned this approach as an unstable representation that may erode democratic principles. This research supports the notion that comedians in politics have become an emerging topic of discussion, one that transcends traditional concerns with celebrity and public favourability. Further studies are recommended to longitudinally explore shifts in discourse coalitions, particularly within Indonesia’s open,  proportional electoral system, which encourages the personalisation of candidates.